2014
DOI: 10.1254/jphs.13174fp
|View full text |Cite
|
Sign up to set email alerts
|

Genipin Inhibits RANKL-Induced Osteoclast Differentiation Through Proteasome-Mediated Degradation of c-Fos Protein and Suppression of NF-κB Activation

Abstract: Abstract. People over the age of 50 are at risk of osteoporotic fracture, which may lead to increased morbidity and mortality. Osteoclasts are responsible for bone resorption in bonerelated disorders. Genipin is a wellknown geniposide aglycon derived from Gardenia jasminoides, which has long been used in oriental medicine for controlling diverse conditions such as inflammation and infection. We aimed to evaluate the effects of genipin on RANKLinduced osteoclast differen tiation and its mechanism of action. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Histone deacetylase inhibitors (HDACis) have exerted potent osteogenic potential related to stability of Runx2 by deacetylases (Kim et al, 2011, Jeon et al, 2006). As such there have been a great number of small molecules or natural products that have been shown to affect osteoclastogenesis (Kim et al, 2014a, Kim et al, 2014a, Lee et al, 2014, Kwak et al, 2010). Although the RANKL/RANK axis is the master regulator for osteoclastogenesis, precise underlying mechanisms for contribution of many coupling factors such as SOST, semaphorin, OSCAR, FcR or OC-STAMP to osteoclastogenesis remains to be explored (Honma et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Histone deacetylase inhibitors (HDACis) have exerted potent osteogenic potential related to stability of Runx2 by deacetylases (Kim et al, 2011, Jeon et al, 2006). As such there have been a great number of small molecules or natural products that have been shown to affect osteoclastogenesis (Kim et al, 2014a, Kim et al, 2014a, Lee et al, 2014, Kwak et al, 2010). Although the RANKL/RANK axis is the master regulator for osteoclastogenesis, precise underlying mechanisms for contribution of many coupling factors such as SOST, semaphorin, OSCAR, FcR or OC-STAMP to osteoclastogenesis remains to be explored (Honma et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study revealed that c-Fos is involved in osteoclast differentiation ( 32 , 33 ). Therefore, the present study investigated the c-Fos expression levels in osteoblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, previous studies indicated that GJE and its active components could improve memory and learning ability, and protect the neurons in animals with brain injury (Sheng et al, 2006 ; Chen et al, 2015 ; Zhang et al, 2016 ). Genipin, a major phytoconstituent of GJE, is a candidate for the treatment of osteoporosis (Hoon Lee et al, 2014 ). GJE was also able to attenuate metabolic syndrome with a combination of other herbal drugs in estrogen-deficient rats (Yang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%